Efektivitas Akupresur dalam Mengurangi Nyeri pada Pasien Gagal Ginjal : Narative Review - Suandika, Made; Inaya, Filia Nadira; Soleha, Putri; Mushthofa, Shidqi (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Chronic Kidney Disease (CKD) is a global health problem that requires patients to undergo long-term hemodialysis therapy. This procedure is frequently associated with various physical and psychological complications, including pain, muscle cramps, anxiety, and decreased quality of life. Pharmacological management of these symptoms has limitations due to potential side effects and the risk of drug dependence, highlighting the need for safe and effective non-pharmacological interventions. This narrative review aims to analyze and synthesize scientific evidence on the effectiveness of acupressure therapy in managing complications experienced by CKD patients undergoing hemodialysis. A total of ten relevant studies were reviewed, focusing on the effects of acupressure on physical symptoms (pain and muscle cramps), psychological symptoms (anxiety), and patients’ quality of life. The findings indicate that acupressure therapy is effective in reducing the intensity and frequency of muscle cramps, alleviating post-hemodialysis headaches, and decreasing anxiety levels. Additionally, acupressure contributes to improvements in overall quality of life among patients receiving regular hemodialysis. In conclusion, acupressure demonstrates significant potential as a complementary non-pharmacological intervention in nursing care for CKD patients undergoing hemodialysis. Further randomized controlled trials with larger sample sizes are recommended to strengthen the existing evidence base.